2020
DOI: 10.3390/genes11050545
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Long Noncoding RNA GAS5 Correlates with Liver Fibrosis in Patients with Nonalcoholic Fatty Liver Disease

Abstract: Background: Advanced liver fibrosis is the most important prognostic factor in nonalcoholic fatty liver disease (NAFLD). The long noncoding RNA (lncRNA), growth arrest-specific transcript 5 (GAS5), is associated with the inhibition of liver fibrogenesis, and its levels are decreased in cirrhotic liver. Methods: We analyzed 51 patients with NAFLD, the diagnosis of which was confirmed by liver biopsy. Expression of GAS5 in both the liver and plasma of the patients was analyzed using a quantitative real-time poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
25
0
4
Order By: Relevance
“…GAS5 can prevent glucocorticoid receptors from being activated and thus control transcriptional activities from its target genes. It is inferred as a potential tumor suppressor and has close correlations with coronary artery disease 50 , cirrhotic livers 51 , coronary artery disease 52 , 53 , rheumatoid arthritis 54 , Parkinson’s disease 55 , and primary glioblastoma 56 .…”
Section: Resultsmentioning
confidence: 99%
“…GAS5 can prevent glucocorticoid receptors from being activated and thus control transcriptional activities from its target genes. It is inferred as a potential tumor suppressor and has close correlations with coronary artery disease 50 , cirrhotic livers 51 , coronary artery disease 52 , 53 , rheumatoid arthritis 54 , Parkinson’s disease 55 , and primary glioblastoma 56 .…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39] Studies have shown that GAS5 is downregulated in experimental liver fibrosis models and human cirrhosis, while another vital study indicated GAS5 is increased in plasma of liver fibrosis patients accompanying the progression of fibrosis degree except for that in cirrhotic livers. 22,40,41 These studies suggest that variations in some ln-cRNAs may be correlated with specific liver diseases, and large patient sample studies are more conducive to elucidating the role of lncRNA in certain diseases. However, the regulatory role of lncRNA nuclearenriched abundant transcript 1 (NEAT1) in diverse liver diseases is poorly understood.…”
Section: F I G U R Ementioning
confidence: 99%
“…In hepatocarcinogenesis, H19 was reported to be decreased in valuable models and exert tumour suppressor function, whereas large patient cohorts reported both up‐ and downregulation of H19 in HCC, which is probably resulted from a panel of studies using rather small sample sizes 37‐39 . Studies have shown that GAS5 is downregulated in experimental liver fibrosis models and human cirrhosis, while another vital study indicated GAS5 is increased in plasma of liver fibrosis patients accompanying the progression of fibrosis degree except for that in cirrhotic livers 22,40,41 . These studies suggest that variations in some lncRNAs may be correlated with specific liver diseases, and large patient sample studies are more conducive to elucidating the role of lncRNA in certain diseases.…”
Section: Introductionmentioning
confidence: 95%
“…GAS5 is a novel non-Ig partner of BCL6. Suppression of GAS5 is associated with clinicopathological characteristics in several liver dysfunctions [112][113][114]. Tumor node stage (TNM), overall survival (OS), disease-free survival (DFS), and metastasis were correlated with GAS5 expression, indicating that GAS5 can be a potential diagnostic and prognostic biomarker in HCC [115].…”
Section: Clinical Application Of Lncrnas and Circrnas As Novel Biomarmentioning
confidence: 99%